Interfacing an EPC Gen 2 UHF RFID reader to a wireless backbone using Zigbee - Anguluan, Abigail
This project interfaces an EPC Gen 2 RFID reader to a wireless backbone using Zigbee modules. Radio frequency communication of an RFID reader to a host makes it possible to work in a larger scale of area/space compared to direct wired communication. The interface using Zigbee modules executes a portion of the IEEE 802.15.4 protocol to achieve a point to point communication. It is an effort towards discovering a substantial use for the IEEE 80.2.15.4 protocol in the RFID area. A wireless bridge between a PC and the SkyeModule M9 RFID reader was established using a Zigbee module connected to each device. The SkyeModule M9 RFID reader was able to function as if it was directly wired to a PC but certain restrictions and limitations apply.